Low-temperature carbonate melt reaction preparation method of compact ceramic film
Through carbonate melt reaction, Na2CO3-K2CO3 eutectic salt is used to dissolve the precursor reactants, achieving low-temperature densification of ceramic films, solving the high energy consumption and element volatility problems during high-temperature sintering, and has industrial application potential.
Patent Information
- Application Number
- CN202311252641.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The sintering process of existing ceramic films requires high temperatures, resulting in high energy consumption, element volatility, segregation and overfired deformation, making it difficult to achieve low temperature densification.
The carbonate melt reaction method was adopted to dissolve the precursor reactant at high melting point by Na2CO3-K2CO3 eutectic salt and react to achieve the preparation of a dense ceramic film at low temperature.
It realizes low-temperature densification of ceramic films, avoids deformation and element volatility caused by high-temperature sintering, saves energy, is cheap, and has industrial application potential.
Smart Images

Figure HDA0004470771830000011 
Figure HDA0004470771830000012 
Figure HDA0004470771830000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional ceramic materials, and in particular relates to a method for densifying a ceramic film at low temperature by utilizing carbonate melt reaction. Background Art
[0002] Sintering densification is a process that transforms loose particles into a solid and dense polycrystalline whole by applying external energy. The temperature required for sintering is usually 1 / 2 to 3 / 4 of the melting point of the material. Due to the limited rate of solid-solid reaction, the sintering temperature of ceramics is usually higher than 1000°C, which is a high-energy consumption process. At the same time, the traditional sintering process is also accompanied by problems such as element volatilization, segregation, overburning deformation, etc., which affect the performance of ceramics.
[0003] The commonly used means to reduce the densification temperature of thin films is to add metal oxide sintering aids or use wet chemical methods to prepare highly active nanopowders for sintering. However, the addition of sintering aids of other metal elements will have an adverse effect on the performance of ceramics and has certain limitations. In recent years, many new sintering technologies have been developed, such as hot pressing sintering with pressure, spark plasma sintering with the introduction of electric fields, and microwave sintering using microwave energy. The external application of energy fields can reduce the sintering difficulty of ceramics to a certain extent and shorten the sintering time. However, the actual operating temperature of some new sintering technologies is as high as 2000℃, which cannot really solve the problems such as element segregation caused by high-temperature sintering; specific devices and equipment are required, which are expensive and difficult to achieve large-scale industrial applications. Therefore, it is necessary to develop a low-temperature densification technology for thin films that is cheap, simple, and easy to scale up industrially. Summary of the invention
[0004] In order to solve the problems of the prior art, the present invention provides a method for low-temperature densification of ceramic films based on carbonate melt reaction. The present invention utilizes the significant advantages of melt growth, such as high crystal purity and good integrity, and introduces Na2CO3-K2CO3 eutectic salt, so that the high-melting-point precursor reactant is dissolved in the eutectic and reacts. After reaching supersaturation, the target product crystal is precipitated and gradually grows and grows together, and finally a micron-level dense ceramic film can be obtained. The present invention utilizes a simple low-temperature melt reaction to avoid deformation, element volatilization segregation and other problems caused by solid-phase high-temperature sintering.
[0005] The present invention provides a method for low-temperature densification of ceramic films based on carbonate melt reaction, comprising the following steps:
[0006] (1) Precursor oxide powder is prepared into a precursor oxide slurry, which is then evenly coated on a substrate and calcined to remove organic matter, thereby obtaining a precursor oxide coating.
[0007] (2) A certain amount of carbonate eutectic powder is mixed evenly with precursor carbonate powder and precursor oxide powder and transferred to an alumina crucible to cover the coating of the embedding step (1).
[0008] (3) placing the crucible of step (2) into a muffle furnace for melt reaction, and after the reaction is completed, pickling and drying are performed to obtain a dense ceramic film.
[0009] The precursor oxide powder is a raw material for preparing ceramic thin films and is a metal oxide;
[0010] The precursor carbonate powder is a raw material for preparing ceramic thin films and is an alkaline earth metal carbonate;
[0011] The carbonate eutectic powder is composed of two alkali metal carbonates; after melting, the eutectic powder dissolves the precursor carbonate powder and the precursor oxide powder, causing them to react with each other, thereby providing a molten environment for crystal growth;
[0012] The melting points of the precursor carbonate and the precursor oxide are both higher than that of the carbonate eutectic powder.
[0013] Furthermore, in the above technical solution, in step (1) and step (2), the precursor oxide powder is TiO2, ZrO2, (ZrO2) 0.92 (Y2O3) 0.08 One of (8YSZ).
[0014] Furthermore, in the above technical solution, the particle size of TiO2 is 10-100nm, the particle size of ZrO2 is 100-500nm, (ZrO2) 0.92 (Y2O3) 0.08 The particle size of (8YSZ) is 10nm~200nm.
[0015] Furthermore, in the above technical scheme, in step (1), surfactant (triethanolamine), dispersant (butyl benzyl phthalate), binder (polyvinyl butyral resin), solvent (ethanol, butanone) and other organic substances are also added to the precursor oxide slurry, and the precursor oxide powder is mixed with the surfactant, dispersant, binder, solvent and other organic substances to obtain the precursor oxide slurry; the percentage content of each component in the precursor oxide slurry is: precursor oxide powder 20-33wt%, ethanol 41-51wt%, butanone 19-20wt%, triethanolamine 1-1.2wt%, polyvinyl butyral resin 3-4wt%, butyl benzyl phthalate 2-3wt%.
[0016] Furthermore, in the above technical solution, in step (1), the coating method is normal pressure or negative pressure impregnation.
[0017] Furthermore, in the above technical solution, in step (1), the substrate is a porous alumina substrate, or a solid oxide battery anode substrate.
[0018] Furthermore, in the above technical solution, in step (1), the pore size of the porous alumina substrate is 1 to 3 μm, and the pore size of the solid oxide battery anode substrate is 1 to 3 μm.
[0019] Furthermore, in the above technical solution, in step (1), the calcination temperature is 400-600° C. and the calcination time is 2-5 hours.
[0020] Furthermore, in the above technical solution, in step (2), the precursor carbonate powder is one of BaCO3 and SrCO3.
[0021] Furthermore, in the above technical solution, in step (2), the carbonate eutectic powder is a mixture of Na2CO3 and K2CO3, the eutectic point is 710°C, the total amount of substance is 0.02 to 0.04 mol, and the amount ratio of Na2CO3 to K2CO3 is 1.2 to 1.6:1.
[0022] Furthermore, in the above technical solution, in step (2), the precursor carbonate powder accounts for 20 to 40 mol% of the carbonate eutectic powder.
[0023] Furthermore, in the above technical solution, in step (2), the added precursor carbonate is in excess of the precursor oxide powder, and the molar ratio of the metal elements in the precursor carbonate powder to the precursor oxide powder is 3:1 to 9:1.
[0024] Furthermore, in the above technical solution, in step (3), the melt reaction temperature is 800 to 900° C.; and the reaction time is 12 to 48 hours.
[0025] Furthermore, in the above technical solution, in step (3), the acid washing is performed by soaking and washing in a 0.5M acetic acid solution overnight.
[0026] Furthermore, in the above technical solution, the thickness of the obtained dense ceramic film is 5 to 10 μm.
[0027] The present invention is beneficial in that:
[0028] (1) Using a simple low-temperature eutectic reaction to prepare dense ceramic films, the refractory reactant powder is dissolved in a suitable molten salt for reaction, thereby transforming the solid-solid system in the traditional sintering method into a more uniform solid-liquid system, greatly improving mass transfer and reaction rate and improving interface contact;
[0029] (2) More importantly, a low-temperature film densification technology has been developed. The densification temperature can be reduced to below 1000°C, avoiding the volatilization of substances and elements, and is expected to be used to grow ceramic films on metal substrates.
[0030] (3) This method saves energy, the raw materials are easily available, the cost is low, the method is simple, the carbonate melt is stable in the air and does not require a specific reaction atmosphere, and does not require expensive equipment, so it has the potential for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the principle of preparing dense ceramic membranes by the low-temperature carbonate melt reaction method described in the present invention.
[0032] Figure 2 This is an electron microscope image of the precursor oxide coating prepared in step 2 of Example 4 of the present invention, wherein a) is the coating surface; b) is the coating cross-section.
[0033] Figure 3 This is an electron microscope image of the dense ceramic membrane prepared in step 3 of Example 4 of the present invention before cleaning, a) is the membrane surface; b) is the membrane cross-section.
[0034] Figure 4 This is an electron microscope image of the dense ceramic membrane prepared in step 3 of Example 4 of the present invention after cleaning, wherein a) is the membrane surface; b) is the membrane cross-section.
[0035] Figure 5 This is an electron microscope image of the dense ceramic film after secondary growth in step 3 of Example 5 of the present invention. DETAILED DESCRIPTION
[0036] The present invention will be further described in the following examples, but the present invention is not limited thereto.
[0037] Example 1
[0038] Preparation of dense BaTiO3 ceramic membrane with Na2CO3-K2CO3 eutectic salt
[0039] Step 1: Preparation of nano-TiO2 coating. Take 20g of nano-TiO2 (particle size of about 40nm) as the starting material, 50g of anhydrous ethanol and 20g of butanone as the solvent, 1.2g of triethanolamine as the surfactant, and mix and mill for 24h, then continue to add 3.6g of butyl benzyl phthalate and 2.7g of polyvinyl butyral as the dispersant and binder and mill for 24h to obtain a uniformly dispersed nano-TiO2 slurry. Each time, the atmospheric pressure is impregnated for 1 minute. The obtained nano-TiO2 slurry is uniformly coated on a porous Al2O3 substrate (diameter 18mm, pore size of about 1μm) by repeating the atmospheric pressure impregnation twice, and then calcined at 500℃ for 3h to remove organic matter.
[0040] Step 2: Prepare a dense BaTiO3 film. Weigh 0.04 mol of Na2CO3 and K2CO3 powder (where the ratio of the amount of Na2CO3 to K2CO3 is 1.6), 0.008 mol of BaCO3 powder and 0.0027 mol of nano-TiO2 powder; that is, BaCO3 accounts for 20 mol% of the total amount of Na2CO3-K2CO3 eutectic salt, and Ba:Ti=3:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover and embed the TiO2 coating of step 1, and place in a muffle furnace to react at 800°C for 24 hours. After the reaction is completed, use 0.5M acetic acid solution to soak and clean overnight, and then dry to obtain a dense BaTiO3 ceramic film.
[0041] Example 2
[0042] Preparation of dense BaZrO3 ceramic membrane with Na2CO3-K2CO3 eutectic salt
[0043] Step 1: Preparation of nano ZrO2 coating. 40g of nano ZrO2 (particle size of about 200nm) was used as the starting material, 50g of anhydrous ethanol and 24g of butanone were used as solvents, and 1.2g of triethanolamine was used as a surfactant and mixed and ball-milled for 24h. Then, 3.6g of butyl benzyl phthalate and 2.7g of polyvinyl butyral were added as dispersants and binders and ball-milled for 24h to obtain a uniformly dispersed nano ZrO2 slurry. A suction flask was used to apply a pressure of -0.05MPa, and the nano ZrO2 slurry was coated on a porous alumina substrate (diameter 18mm, pore size of about 1μm) by negative pressure impregnation, and the impregnation time was 1min.
[0044] Step 2: Prepare a dense BaZrO3 film. Weigh 0.04 mol of Na2CO3 and K2CO3 powder (where the ratio of Na2CO3 to K2CO3 is 1.2), 0.016 mol of BaCO3 powder and 0.0017 mol of nano ZrO2 powder; that is, BaCO3 accounts for 40 mol% of the total amount of Na2CO3-K2CO3 eutectic salt, and Ba:Zr=9:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover and embed the ZrO2 coating of step 1, and place in a muffle furnace to react at 850°C for 48 hours. After the reaction is completed, use 0.5M acetic acid solution to soak and clean overnight, and then dry to obtain a dense BaZrO3 ceramic film.
[0045] Example 3
[0046] Preparation of dense SrTiO3 ceramic membrane with Na2CO3-K2CO3 eutectic salt
[0047] Step 1: Prepare nano-TiO2 coating. Same as step 1 in Example 1.
[0048] Step 2: Prepare a dense SrTiO3 film. Weigh 0.02 mol of Na2CO3 and K2CO3 powder (where the ratio of Na2CO3 to K2CO3 is 1.5), 0.006 mol of SrCO3 powder and 0.001 mol of nano-TiO2 powder; that is, SrCO3 accounts for 30 mol% of the total amount of Na2CO3-K2CO3 eutectic salt, Sr:Ti=6:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover and embed the TiO2 coating of step 1, and place in a muffle furnace to react at 900°C for 12 hours. After the reaction is completed, use 0.5M acetic acid solution to soak and clean overnight, and then dry to obtain a dense SrTiO3 ceramic film.
[0049] Example 4
[0050] Preparation of dense BaZr by Na2CO3-K2CO3 eutectic salt 0.85 Y 0.15 O 3-δ (BZY) Solid Oxide Electrolyte Membrane
[0051] Step 1: Prepare the BZY solid oxide battery anode support layer. BaCO3, Y2O3, and ZrO2 are added in a stoichiometric ratio, and NiO and 8μm spherical graphite are added. A porous BZY anode support layer (16mm in diameter after sintering, 1-3μm in pore size) is prepared by tape casting and sintered at 1500℃ for 6h, wherein the mass ratio BZY:NiO=4:6, and the spherical graphite accounts for 20% of the total mass.
[0052] Step 2: Preparation of Nano(ZrO2) 0.92 (Y2O3) 0.08 (8YSZ) coating. 10g of nano-8YSZ (particle size of about 10nm) and 10g of micro-nano-8YSZ (particle size of about 200nm) powder were used as starting materials, 50.4g of anhydrous ethanol and 20g of butanone were used as solvents, and 1.2g of triethanolamine was used as a surfactant and mixed and ball-milled for 24h. Then, 3.6g of butyl benzyl phthalate and 2.7g of polyvinyl butyral were added as dispersants and binders and ball-milled for 24h to obtain a uniformly dispersed 8YSZ slurry. The immersion was repeated twice at normal pressure for 1min, and the 8YSZ was coated on the polished BZY anode substrate, and calcined at 500℃ for 3h to remove organic matter.
[0053] Step 3: Prepare a dense BZY electrolyte membrane. Weigh 0.02 mol of Na2CO3 and K2CO3 powders (wherein the ratio of the amount of Na2CO3 to K2CO3 is 1.2), 0.004 mol of BaCO3 powder and 0.0004 mol of nano 8YSZ powder respectively; that is, BaCO3 accounts for 20 mol% of the total mass of Na2CO3-K2CO3, and Ba:(Zr+Y)=9:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover and embed the 8YSZ coating of step 2, put into a muffle furnace and react at 800°C for 12 hours. After the reaction is completed, the morphology before cleaning is as follows. Figure 3 As shown. After overnight soaking and cleaning with 0.5M acetic acid solution, a dense BZY electrolyte membrane with a thickness of about 10μm was obtained after drying. The morphology after cleaning is as follows Figure 4 shown.
[0054] Example 5
[0055] Preparation of dense BZY solid oxide electrolyte membrane by secondary growth of Na2CO3-K2CO3 eutectic salt
[0056] Step 1: Prepare the BZY solid oxide battery anode support layer, which is the same as step 1 in Example 4.
[0057] Step 2: Preparation of Nano(ZrO2) 0.92 (Y2O3) 0.08 (8YSZ) coating. Same as step 2 of Example 4.
[0058] Step 3: Prepare a dense BZY electrolyte membrane. Weigh 0.02 mol of Na2CO3 and K2CO3 powders (the ratio of the amount of Na2CO3 to K2CO3 is 1.2), 0.004 mol of BaCO3 powder and 0.0004 mol of nano 8YSZ powder respectively; that is, BaCO3 accounts for 20 mol% of the total mass of Na2CO3-K2CO3, and Ba:(Zr+Y)=9:1 mol / mol. After fully grinding and mixing, transfer to an alumina crucible, cover with the 8YSZ coating of step 2, and place in a muffle furnace to react at 800°C for 12 hours. Repeat the above ratios and steps for secondary growth. Use 0.5M acetic acid solution to soak and clean overnight, and then dry to obtain a BZY electrolyte membrane. The morphology after secondary growth is as follows: Figure 5 shown.
[0059] Many embodiments can be listed above. For example, the grain size of the film can be changed by adjusting the reaction temperature or time. In addition, the density of the film can be further improved by repeated growth. The ratio of the carbonate eutectic to the precursor carbonate and the ratio of the precursor carbonate to the precursor oxide are both adjustable. In theory, as long as the precursor carbonate and the precursor oxide can be dissolved in the molten eutectic salt to react, and the reaction products can reach supersaturation in the melt and precipitate, a dense ceramic film can be prepared according to the carbonate melt reaction method proposed in the present invention.
Claims
1. A method for low-temperature densification of ceramic films based on carbonate melt reaction, characterized in that: The method comprises the following steps: (1) preparing a precursor oxide powder into a slurry, uniformly coating the slurry on a substrate, and calcining the slurry to remove organic matter, thereby obtaining a precursor oxide coating; (2) mixing the carbonate eutectic powder, the precursor carbonate powder and the precursor oxide powder uniformly, transferring the mixture to an alumina crucible, and covering and encapsulating the coating prepared in step (1); (3) placing the crucible of step (2) into a muffle furnace for melt reaction, followed by pickling and drying to obtain a dense ceramic film; The precursor oxide powder is a metal oxide, the precursor carbonate powder is an alkaline earth metal carbonate, and the carbonate eutectic powder is composed of two alkali metal carbonates.
2. The method according to claim 1, characterized in that: In step (1) and step (2), the precursor oxide powder is TiO2, ZrO2, (ZrO2) 0.92 (Y2O3) 0.08 One of them.
3. The method according to claim 1, characterized in that: In step (1), triethanolamine, butyl benzyl phthalate, polyvinyl butyral resin, ethanol and butanone are further added to the slurry, and the percentage of each component in the slurry is: 20-33wt% of precursor oxide powder, 41-51wt% of ethanol, 19-20wt% of butanone, 1-1.2wt% of triethanolamine, 3-4wt% of polyvinyl butyral resin, and 2-3wt% of butyl benzyl phthalate.
4. The method according to claim 1, characterized in that In step (2), the carbonate eutectic powder is a mixture of Na2CO3 and K2CO3, wherein the molar ratio of Na2CO3 to K2CO3 is 1.2 to 1.6:
1.
5. The method according to claim 1, characterized in that: In step (2), the precursor carbonate powder is one of BaCO3 and SrCO3, and the precursor carbonate powder accounts for 20 to 40 mol% of the carbonate eutectic powder.
6. The method according to claim 1, characterized in that In step (2), the molar ratio of the metal elements in the precursor carbonate powder to the precursor oxide powder is 3:1 to 9:
1.
7. The method according to claim 1, characterized in that In step (3), the temperature of the melt reaction is 800-900° C. and the time is 12-48 hours.
8. The method according to claim 1, characterized in that: In step (1), the coating method is atmospheric pressure or negative pressure impregnation, and the substrate is a porous alumina substrate or a solid oxide battery anode substrate.
9. The method according to claim 1, characterized in that: In step (1), the calcination temperature is 400-600° C. and the calcination time is 2-5 hours.
10. The method according to claim 1, characterized in that The obtained dense ceramic film has a thickness of 5 to 10 μm.